Applying Aristotle's three ancient rhetorical appeals to modern business communication - Morrell, Kevin (London : SAGE Publications: SAGE Business Cases Originals, 2020)
Though the term rhetoric is often used nowadays in a negative sense, the word and concept have origins in antiquity. In ancient philosophy, rhetoric is a neutral term used to describe the science and art of persuasion. The case introduces a simple, three-part structure for understanding rhetoric. The ancient philosopher Aristotle describes three kinds of rhetorical appeal speakers can make to their audiences: the appeal to the speaker's character which he calls ethos; the appeal to reason which he calls logos; and the appeal to the emotions of the audience which he calls pathos. The most effective speeches often combine these appeals. Even though Aristotle was discussing rhetoric in ancient Greece, these three appeals are still used today. To show this in action, the case includes two extracts: one is taken from a famous political document and the second is from a legendary speech by Steve Jobs. If we are a watchful audience and can be aware of these appeals it can be easier to hold speakers to account for what they say and not just how they say it. This can be beneficial when we are employees and have to evaluate the claims made by our senior managers. It can help us as consumers who want to weigh up the claims of advertisers. It can also help if we are citizens listening to politicians who want our vote.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Communication in organizations; Management -- Communication systems